PENGARUH TERAPI AKUPRESUR TERHADAP INTENSITAS NYERI HAID (DISMENORE) PADA MAHASISWA KEBIDANAN INSTITUT KESEHATAN MITRA BUNDA 2020 - Siti Husaidah (Poltekkes Kemenkes Padang, 2021)
The period of menarche in Indonesia has reached 60-70% who experience dysmenorrhea and cause women to be unable to carry out activities and reduce women's quality of life. This study aims to describe the effect of acupressure therapy on the intensity of menstrual pain. This type of quantitative research is a quasi-experimental design with a one group pretest-posttest approach with sampling using a purposive sampling technique using 100 respondents from April 20 to June 21 2020. The data was obtained from a questionnaire and processed using the Wilcoxon test. The results showed the overall data of the variable dysmenorrhea pre test - post test in the intervention group Asymp value. The significance is 0.000 <0.05, while the control group has Asymp value. The significance is 1,000 > 0.05, so it can be concluded that the results of the analysis of changes in the pain scale pre-test - post-test in the intervention group showed a significant change between the pre-test and post-test pain scales. It can be seen from the measurement results of the Mean Rank pain scale before therapy is 0.00 and Mean Rank after therapy is 25.50 which means there is a decrease in the intensity of menstrual pain. Based on the results of the research above, adolescents need to add information and understanding through various mass media to equip themselves in dealing with complementary menstrual pain